Exercises 2.5
Solving these equations simultaneously, we obtain
n
=1and
m
=1
. So
,
µ
(
x, y
)=
xy.
With these choices for
n
and
m
we obtain the exact equation
(2
xy
3
−
6
x
2
y
2
)
dx
+(3
x
2
y
2
−
4
x
3
y
)
dy
=0
.
Solving this equation, we have
F
(
x, y
)=
Z
(2
xy
3
−
6
x
2
y
2
)
dx
=
x
2
y
3
−
2
x
3
y
2
+
g
(
y
)
⇒
F
y
(
x, y
)=3
x
2
y
2
−
4
x
3
y
+
g
0
(
y
)=
N
(
x, y
)=3
x
2
y
2
−
4
x
3
y.
Therefore,
g
0
(
y
) = 0. Since the constant of integration can be incorporated into the constant
C
of the solution, we can pick
g
(
y
)
≡
0. Thus, we have
F
(
x, y
)=
x
2
y
3
−
2
x
3
y
2
and the solution becomes
x
2
y
3
−
2
x
3
y
2
=
C.
Since we have multiplied the original equation by
This is the end of the preview.
Sign up
to
access the rest of the document.
 Spring '10
 Hald,OH
 Math, Differential Equations, Calculus, Linear Algebra, Algebra, Equations, Derivative, Expression, Trigraph

Click to edit the document details